Ordinance No. 32: An Ordinance to Define Misdemeanors and Provide Penalty Therefor, and for Other Purposes, THE DAILY MORNING ALASKAN, Jun. 18, 1903, at 2 (Skagway, Alaska). §10 - (:unkn) unknown (General Publisher, 1903)
Prohibited concealed carry of any weapon. Violators guilty of a misdemeanor, punishable by fine of not more than fifty dollars, or imprisonment in jail of not more than thirty days, or both.
--
Keywords: CARRY - CONCEALED